2016
DOI: 10.2147/ccide.s63626
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to manage patients with dental anxiety and dental phobia: literature review

Abstract: Dental anxiety and phobia result in avoidance of dental care. It is a frequently encountered problem in dental offices. Formulating acceptable evidence-based therapies for such patients is essential, or else they can be a considerable source of stress for the dentist. These patients need to be identified at the earliest opportunity and their concerns addressed. The initial interaction between the dentist and the patient can reveal the presence of anxiety, fear, and phobia. In such situations, subjective evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
409
2
52

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(468 citation statements)
references
References 88 publications
5
409
2
52
Order By: Relevance
“…sight (air-turbine drill, needles), sounds (drilling), sensations (high-frequency vibrations [the annoyance factor]), and smells can help alleviate anxiety [13]. Besides that, 73% of parents believed the presence of parents during the procedure might influence child's behaviour but however, a study…”
Section: Discussionmentioning
confidence: 99%
“…sight (air-turbine drill, needles), sounds (drilling), sensations (high-frequency vibrations [the annoyance factor]), and smells can help alleviate anxiety [13]. Besides that, 73% of parents believed the presence of parents during the procedure might influence child's behaviour but however, a study…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that dental procedures might induce patient stress and thus affect the cardiovascular system [3]. In normal children, the pulse is frequently found to increase in the dental environment due to anxiety [5]. Many treatments, which have been found to be effective in decreasing anxious and disruptive behavior, consist of a package of interventions [8].…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Institutes of Health, a rapid pulse or arrhythmia may occur during episodes of anxiety [4]. Normally, in children, the pulse is frequently found to increase in the dental environment due to anxiety [5]. If patients are not managed appropriately, it is quite possible to establish what has been referred to as a "vicious cycle of dental fear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations